Avaliação do Programa Saúde da Família em municípios do Nordeste brasileiro: velhos e novos desafios An assessment of the Family Health Program in municipalities of Northeast Brazil: old and new challenges - Paulo de Medeiros Rocha; Alice da Costa Uchoa; Nadja de Sá Pinto Dantas Rocha; Elizabethe Cristina Fagundes de Souza; Marconi de Lima Rocha; Themis Xavier de Albuquerque Pinheiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Este artigo apresenta parte dos resultados referentes à pesquisa avaliativa Estudos de Linha de Base, desenvolvida em 21 municípios com mais de 100 mil habitantes em três estados do Nordeste do Brasil. O objetivo geral foi avaliar experiências de implementação do Programa Saúde da Família (PSF), com foco nas induções do PROESF. Foi realizada Análise de Implantação utilizando-se como método o estudo de caso. Na análise utilizaram-se as dimensões: político-institucional, organização da atenção e cuidado integral. Como avanços destacam-se: priorização do PSF em áreas de risco; aprendizado institucional, qualificação dos gestores e equipes; centrais de regulação, vínculo e percepção positiva sobre PSF. Em relação aos desafios observaram-se: fortalecimento da capacidade formuladora local, alocação dos recursos na Atenção Básica, desprecarização do trabalho, efetivação de rede de atenção, fortalecimento da participação social, qualificação do monitoramento e avaliação para tomada de decisão; acolhimento; filas para exames, consultas e internação; implementação do trabalho em equipe e atividades promocionais e intersetoriais. This article presents part of the results from the Baseline Studies, an evaluative research conducted in 21 municipalities with more than 100,000 inhabitants each, in three States of Northeast Brazil. The overall objective was to assess experiences in the implementation of the Family Health Program (FHP), with a focus on inductions in the PROESF. An implementation analysis was performed, using the case study method. The analysis focused on these dimensions: political-institutional, health organization, and comprehensive care. Outstanding advances included: prioritize the FHP in high-risk areas; institutional learning, with qualification of managers and teams; definition of institutional levels for regulating the FHP; and health team-user bonds and positive perceptions concerning the program. Challenges included: strengthening of local policy and decision-making capacity; allocation of primary care resources; greater employment security for human resources; effective implementation of the health care network; strengthening of social participation; upgrading of monitoring and evaluation for decision-making; receptivity; waiting lines for tests, appointments, and hospital admissions; implementation of teamwork; health promotion and inter-sector activities.